CHEMO PREVENTIVE EFFECTS OF ACTINOBACTERIAL STRAIN SNI5 EXTRACT ON N-NITROSODIETHYLAMINE INDUCED CANCER (COLON) ACTIVITY IN MICE - N.S. SWARNAKUMAR,; E. DILIPAN, (International Journal of Pharma and Bio Sciences, 2015)
The present study is designed to investigate the preventive effects of actinobacterial extract on colon carcinogenesis in NDEA induced mice tumor. Twenty four mice were divided into four groups of six animals each. Animals (Group I) proceed as the control without any treatment. Animals (Group II) were intraperitonially injected with N-nitrosodiethylamine at three doses at an interval for ten days so as to induce colon cancer. Animals (Group III) were orally administrated of actinobacterial strain SNI5 extract. Animals (Group IV) were administered orally with actinobacterial extract and N-nitrosodiethylamine. The present study demonstrated that the actinobacterial extract effectively prevented the formation of preneoplastic foci in mice when given along with the NDEA treatment i.e. during the inhibition phase and often the NDEA treatment until the end of the experiment. Therefore, the present investigation demonstrated that the actinobacterial extract SNI5 seems to be a potential, and a promising chemopreventive agent.